2016
DOI: 10.3232/sjss.2016.v6.n2.06
|View full text |Cite
|
Sign up to set email alerts
|

Available phosphorus in the central area of the Argentinean Pampas. 2: Kinetics of adsorption and desorption of phosphorus under different soil and management environments

Abstract: The concentration of phosphate ions in solution is critical in defining the ability of a soil to adequately meet crop demand. That concentration is regulated by adsorption/desorption and precipitation/dissolution processes, particularly its kinetics of reaction. This work was developed in order to find the kinetic model describing the sorption/desorption of phosphate in soils of the Argentinean Pampas region, to describe the processes associated with these reactions and to define the effect of temperature on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, such a ratio is not relevant in a typical low temperature geochemical environment such as P rich agricultural soils in the Midwestern U.S. The Ca/P ratio in P rich agricultural soils is in a range of 8–86 in the different regions of alfisols in the U.S., which had relatively abundant Ca because of at least 35% base saturation. In the case of mollisols with >50% base saturation, the ratio is as high as 226. Since there is no comprehensive data of dissolved Ca and P concentrations in soil pore waters in the literature, it is difficult to assess the actual Ca/P ratio in soil solutions.…”
Section: Methodsmentioning
confidence: 99%
“…However, such a ratio is not relevant in a typical low temperature geochemical environment such as P rich agricultural soils in the Midwestern U.S. The Ca/P ratio in P rich agricultural soils is in a range of 8–86 in the different regions of alfisols in the U.S., which had relatively abundant Ca because of at least 35% base saturation. In the case of mollisols with >50% base saturation, the ratio is as high as 226. Since there is no comprehensive data of dissolved Ca and P concentrations in soil pore waters in the literature, it is difficult to assess the actual Ca/P ratio in soil solutions.…”
Section: Methodsmentioning
confidence: 99%
“…P sorption kinetic analysis showed that the soil became saturated with P, thereby affecting the rate of P sorption, specifically at manure application rates above CM20. At higher treatments of CM20-CM40, the rate of P sorption decreased significantly, indicating that the sorption sites were saturated with P. According to Silva Rossi et al (2016), the history of fertilization or P addition significantly affected the rate of P sorption through the binding mechanism of the soil sorption site. Consequently, the rate of P sorption influenced the optimal timing of fertilization (Guppy et al, 2005).…”
Section: Figure 3 P Uptake By Wheatmentioning
confidence: 99%